Pengaruh Persentase Katalis pada Pembuatan Perekat Kayu Cair terhadap Daya Rekatnya sebagai Bahan Perekat Substitusi Fenol Formaldehida pada Pembuatan Kayu Lapis The Effects of Catalyst Percentage Used in Producing Wood Liquid on Its Bond Strength as Phenol Formaldehyde Substitute Adhesive in Plywood Production - Bambang Prasetya; Euis Hermiati; Sudijono Sudijono (Jurnal Ilmu dan Teknologi Kayu Tropis, 2004)
The aim of this research was to study the effects of percentage of catalyst used in producing wood liquid (WL) on its bond strength as Phenol Formaldehyde (PF) substitute adhesive in plywood production.  Albizia (Paraserianthes falcataria) wood flour passed 60 mesh sieves having around 5% moisture content was liquefied in phenol solution.  Catalyst used, sulfuric acid 98%, was added at the level of 1%,  2% and 3% of the total phenol solution.  The wood liquid obtained was observed and measured for its physico-chemical properties, including color, total solid, pH, specific gravity and viscosity.  The degrees of PF substitution tried were 100/0, 80/20, 60/40, 40/60 and 20/80 (PF/WL).  Those adhesive mixtures were used in the preparation of plywood made of Meranti (Shorea sp.) and Keruing (Dipterocarpus spp.).  Bond strength of the plywood samples were determined based on the Indonesian National Standard (SNI 01 – 2704 – 1992).  Results of the research showed that Albizia wood flour could be completely liquefied by phenol and sulfuric acid.  Bond strength testing of exterior grade plywood samples of Meranti showed that a quite high percentage of catalyst (3%) decreased bond strength, while that of Keruing showed that the higher the percentage of catalyst, the higher the bond strength.  In general, adhesive composition of 80/20, 60/40 and some 40/60 (PF/WL) can be used as plywood adhesive and meet the SNI for plywood.